Differential response of cocoa (Theobroma cacao) families to field establishment stress. Issue 2 (13th February 2013) - Padi, Francis Kwame; Adu‐Gyamfi, Paul; Akpertey, Abraham; Arthur, Alfred; Ofori, Atta; Weber, W. E.
Abstract High seedling mortality during the establishment phase of cocoa has become a critical constraint to sustainable cocoa farming. The objective of this study was to develop varieties with higher seedling survival compared with cultivars currently recommended for planting in denuded regions. Thirty‐seven families composed into two sets of 18 (families from recommended clones) and 19 (families from recently introduced clones) were evaluated for field survival under full sunlight and dry weather conditions. Families differed significantly for vigour (increase in trunk cross‐sectional area, TCSA) and percentage of survived seedlings by the end of the dry weather conditions. Survival and vigour were significantly correlated in only one set of families. The contribution of general combining ability (GCA) to seedling survival was low to moderate. An Amelonado clone and clones from the Iquitos genetic group had negative GCA estimates for both increase in TCSA and survival. Clones of Scavina origin had the most positive contribution to survival. The key outcome of the study was that cocoa families with higher establishment success can be obtained from the currently available germplasm.